Counteraction to the system and anti-system in the Strugatsky brothers' story "Snail on the slope" - I. V. Bratus, (Ukrainian Cultural Studies, 2021)
Aspects of countering the system and anti-system are considered in the Strugatsky brothers ' novel "Snail on the slope". It is proved that science fiction writers managed to recreate quite complex aspects of the interaction of various systems within the framework of literary heritage. The broad palette of writers has absorbed an understanding of contradictions with underlying causes. In this article, some aspects of the interaction of the individual and the system, systems and anti-systems are demonstrated. Special attention is paid to the Soviet realities, which became the basis for the artistic picture of the fantastic world. This indicates the uniqueness of "Snail on the slope". One of the unique qualities is the influence on the story "Snail on the slope" by Franz Kafka (novels "The Process", "The Castle"). When analyzing the story, the focus of countering the system and the anti-system is transferred to the idea of the future. It is proved that the writers abandoned the continuous optimistic model of the future inherent in their earlier works. Strugatsky brothers have worked out in detail the mechanism of the inability to evolve into the future without radical changes in the essence of man. The literature of the second half of the twentieth century contains an extraordinary potential for understanding our current realities. Somewhere we are even in a more "winning" position – the authors and readers of that time had a more narrowed range of analysis, which was naturally inherent in "their time". At the same time, we are also partially vulnerable, especially in the historical and cultural context. Because the time of writing a work leaves an imprint on its content, the keys to its understanding are often in the social parallels of everyday life, which is fully understood by contemporaries, and "descendants" need to explain certain specific aspects of everyday life, psychological model or banal meaning of a particular word (they become anachronisms or acquire a different meaning). At the same time, it is worth paying attention to those questions that are transcendental in nature. Strugatsky brothers in "Snail on the Slope" experienced a corresponding experience – they tried to create a multi-faceted picture of the world with "their own" laws. At the same time, the task they set was not only to come up with, but also to "guess" the true concept, to bring the artistic fabric of the work closer to the "truth of life". Therefore, this work is fundamentally different from a significant part of their literary heritage, it is a kind of "experimental platform". They did not try to repeat this experience in their future work.
Keywords: fiction, Strugatsky, system, anti-system, literature, Kafka, USSR